Numerical evaluation for Cauchy type singular integrals using modification of discrete vortex method and spline approximation - Eshkuvatov, Zainiddin K.; Nik Long, Nik Mohd Asri (Universiti Putra Malaysia Press, 2007)
This paper deals with the construction of an efficient quadrature formula for singular integrals (SI) of Cauchy type based on modification of discrete vortex method (MDV) and interpolation linear spline. The estimations of errors are obtained in the classes of Hα(K, [-1,1]) and C1([-1,1]). Numerical analysis are also given.